القدرة التنافسية لمنتجات الفستق السوري دراسة تحليلية مقارنة وفق المؤشرات الدولية - الفحل, حسين; البوش, سامر علي (Latakia University Journal - Economic and Legal Sciences Series, 2014)
تم في هذا البحث تناول أهم المؤشرات التنافسية لصادرات الفستق السوري, حيث تم تحليل بيانات منظمة التجارة العالمية لهذه المؤشرات والتوصل من خلالها إلى نتائج توضح الوضيعة التنافسية لمنتج الفستق السوري. إذ تم تحليلها بشكل منفرد أولاً ليتبين أن صادرات هذا المنتج ذات حصة سوقية جيدة على المستويين المحلي والدولي وذات مستوى توافقي جيد مع متطلبات الأسواق الدولية والإقليمية, وهي قادرة على تلبية مختلف أنماط الطلب العالمي من حيث الجودة والسعر والتجانس, ولها القدرة على الاندماج مع مختلف أطياف الطلب الخارجي لذلك المنتج, كما تعتبر شديدة التركُّز في صادراتها بسبب اعتمادها وتركيزها على مجموعة محدودة من أصناف وأشكال هذا المنتج في التصدير, أما عند مقارنة تلك المؤشرات مع مؤشرات الدول الأخرى المنتِجة للفستق فإن نتائج التحليل تشير إلى أن المؤشرات السورية هي من أفضل المؤشرات على المستوى العالمي بعد كل من إيران وأمريكا وتركيا, ولكنها تحتاج إلى إضافات تكنولوجية أكثر مما هي عليه, لتتمكن من زيادة القيمة المضافة في هذا المنتج, إضافةً لحاجتها إلى استثمارات إضافية من شأنها تحقيق إنتاج أكبر وحصة تصديرية أعلى . In this paper, taking most important indicators of the competitiveness of Syrian pistachio exports, where data were analyzed WTO to reach these indicators and which to menial describes results competitiveness of Syrian pistachio product. It has been analyzed individually first to prove that the exports of this product way good market share both domestically and internationally, and with the level of harmonic well with the requirements of the international markets and regional and are able to meet the patterns of global demand in terms of quality and price, and have the ability to integrate with various spectrums external demand for that product, and are highly concentrated in exports because of its dependence and its focus on a limited range of varieties of this product in the export, but when you compare these indicators with indicators of other countries producing pistachio, the results of the analysis indicate that the indicators Syria is one of the best indicators at the global level after both Iran and the United States and Turkey, but they need to technological additions more than it is to be able to increase the added value in this product, in addition to the need for additional investments that will achieve greater production and higher export share.